Trichinella spp. in Wild Boars (Sus scrofa), Brown Bears (Ursus arctos), Eurasian Lynxes (Lynx lynx) and Badgers (Meles meles) in Estonia, 2007–2014 - Age Kärssin; Liidia Häkkinen; Annika Vilem; Pikka Jokelainen; Brian Lassen (Animals, 2021)
In this study, we summarize Trichinella findings from four wild, free-ranging host species from Estonia during 2007–2014. Trichinella spp. larvae were detected in 281 (0.9%, 95% confidence interval (CI) 0.8–1.0) of 30,566 wild boars (Sus scrofa), 63 (14.7%, 95% CI 11.6–18.3) of 429 brown bears (Ursus arctos), 59 (65.56%, 95% CI 55.3–74.8) of 90 Eurasian lynxes (Lynx lynx), and three (60.0%, 95% CI 18.2–92.7) of five badgers (Meles meles). All four European Trichinella species were detected: T. britovi in 0.7% of the wild boars, 7.2% of the brown bears, 45.6% of the lynxes, and 40.0% of the badgers; T. nativa in 0.1% of the wild boars, 5.8% of the brown bears, and 20.0% of the lynxes; T. pseudospiralis in 0.02% the wild boars; and T. spiralis in 0.03% of the wild boars and 4.4% of the lynxes. The results include the first description from Estonia of T. britovi in brown bear and badgers, T. pseudospiralis in wild boars, and T. spiralis in wild boars and lynxes. The results indicate high infection pressure in the sylvatic cycles across the years—illustrating continuous risk of spillover to domestic cycles and of transmission to humans.